Program Pengembangan Agrobisnis Holtikultura dengan Metode Policy Analysis Matrix - Notoatmojo, Budiman; Sarjono, Haryadi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
In general, the purpose of this study is to find out the level of success of the development program of horticultural based agribusiness administered by the Directorate General of Horticultural Plant Production Development. This study uses macro indicators including production development and productivity of horticultural commodity, development of national added value, and development of contributions to the national food self sufficiency; while the micro indicators include profitability level of the horticultural agribusiness, competitive level, and the issues and problems that must be faced while the PPAH program is in progress.